2021
DOI: 10.1155/2021/6617750
|View full text |Cite
|
Sign up to set email alerts
|

Nonpenalty Machine Learning Constraint Handling Using PSO‐SVM for Structural Optimization

Abstract: Firstly formulated to solve unconstrained optimization problems, the common way to solve constrained ones with the metaheuristic particle swarm optimization algorithm (PSO) is represented by adopting some penalty functions. In this paper, a new nonpenalty-based constraint handling approach for PSO is implemented, adopting a supervised classification machine learning method, the support vector machine (SVM). Because of its generality, constraint handling with SVM appears more adaptive both to nonlinear and disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…Although the PSO algorithm already possesses two kinds of memories (cognitive and social), most of the information about the swarm visited positions is discarded, and a better exploitation of the past particles positions remains to be fully determined. In another recent work [18], a first promising step in that direction has been already made. In [18], the PSO has been hybridized with a machine learning algorithm, the support vector machine (SVM).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the PSO algorithm already possesses two kinds of memories (cognitive and social), most of the information about the swarm visited positions is discarded, and a better exploitation of the past particles positions remains to be fully determined. In another recent work [18], a first promising step in that direction has been already made. In [18], the PSO has been hybridized with a machine learning algorithm, the support vector machine (SVM).…”
Section: Discussionmentioning
confidence: 99%
“…In a different recent contribution of the authors [18], some further novel approaches to deal with constraints have been presented, considering a hybridization of the PSO with a machine learning support vector machine. However, the current paper presents a completely different approach based on handling constraints directly based on information which can be retrieved from the swarm positions in terms of objective function and constraints violations.…”
Section: Introductionmentioning
confidence: 99%
“…The design indexes of reflector are affected by many independent dimensional parameters, which include the height of the reflector (x 1 ), the spacing distance of the reinforcement (x 2 ), the thickness of the reinforcement (x 3 ), the wall thickness of the outer ring of the reflector (x 4 ) and the minimum mirror thickness of the reflector (x 5 ). The functional relationship between the input random variables and the output response is shown in Equation ( 7)- (9).…”
Section: Preliminary Work For Reflectormentioning
confidence: 99%
“…Li used topology optimization and integration analysis for the lightweight design and mounting of a 760 mm diameter SiC reflector [6]. In addition to the above-mentioned topology optimization methods, intelligent algorithms and surrogate models have been applied to the optimal design of mechanical structures in recent years [7][8][9][10][11][12]. Kihm et al used genetic algorithm to optimize the dimensional parameters of the mirror [13].…”
Section: Introductionmentioning
confidence: 99%
“…e results showed that the proposed approach was sufficiently general and robust to handle structural configuration having significantly different structural deficiencies. Rosso et al [14] proposed a new nonpenalty-based constraint handling approach for particle swarm optimization, adopting a supervised classification machine learning method, the support vector machine. e results showed that the new approach represented a valid alternative to solve constrained optimization problems even in structural optimization field.…”
Section: Introductionmentioning
confidence: 99%